The Beneficial Effects of Minimizing Blood Loss in Pancreatoduodenectomy. Issue 1 (July 2019) - Seykora, Thomas F.; Ecker, Brett L.; McMillan, Matthew T.; Maggino, Laura; Beane, Joal D.; Fong, Zhi Ven; Hollis, Robert H.; Jamieson, Nigel B.; Javed, Ammar A.; Kowalsky, Stacy J.; Kunstman, John W.; Malleo, Giuseppe; et al.
Abstract : Objective: The aim of this study was to elucidate the impact of intraoperative blood loss on outcomes following pancreatoduodenectomy (PD). Background: The negative impact of intraoperative blood loss on outcomes in PD has long been suspected but not well characterized, particularly those factors that may be within surgeons' control. Methods: From 2001 to 2015, 5323 PDs were performed by 62 surgeons from 17 institutions. Estimated blood loss (EBL) was discretized (0 to 300, 301 to 750, 751 to 1300, and >1300 mL) using optimal scaling methodology. Multivariable regression, adjusted for patient, surgeon, and institutional variables, was used to identify associations between EBL and perioperative outcomes. Factors associated with both increased and decreased EBL were elucidated. The relative impact of surgeon-modifiable contributors was estimated through beta coefficient standardization. Results: The median EBL of the series was 400 mL [interquartile range (IQR) 250 to 600]. Intra-, post-, and perioperative transfusion rates were 15.8%, 24.8%, and 37.2%, respectively. Progressive EBL zones correlated with intra- but not postoperative transfusion in a dose-dependent fashion ( P < 0.001), with a key threshold of 750 mL EBL (8.14% vs 40.9%; P < 0.001). Increasing blood loss significantly correlated with poor perioperative outcomes. Factors associated with increased EBL were trans-anastomotic stent placement, neoadjuvant chemotherapy, pancreaticogastrostomy reconstruction, multiorgan or vascular resection, and elevated operative time, of which 38.7% of the relative impact was "potentially modifiable" by the surgeon. Conversely, female sex, small duct, soft gland, minimally invasive approach, pylorus-preservation, biological sealant use, and institutional volume (≥67/year) were associated with decreased EBL, of which 13.6% was potentially under the surgeon's influence. Conclusion: Minimizing blood loss contributes to fewer intraoperative transfusions and better perioperative outcomes for PD. Improvements might be achieved by targeting modifiable factors that influence EBL. Abstract : Supplemental Digital Content is available in the text